Telecomunications in european union and the information society - Erginoğlu, Ö. Alim (My University, 1999)
Driven by unrelenting technological and market forces, telecommunications is today one of the world's dynamic economic sector. Until not long ago a relatively obscure territory of interest mainly to engineers, telecommunications today seem to be everybody's proper playing field. Large and small businesses, user groups, investment banks, policy makers, development organizations, legislators, economists, political scientists, consumers, students and lawyers, among others, are now also actively and visibly involved in telecommunications. Traditionally, telecommunications was regarded as a relatively straightforward public utility. Economies of scale, political and military sensitivities, and large externalities made telecommunications a typical public service believed to be a natural monopoly. In this environment, telecommunications development focused mainly on extending standard service, building basic networks, and improving the performance of the operating entities. The main issues were technological, and management of telecommunications enterprises was largely oriented toward engineering. Research in the 1960s and 1970s documented the importance of telecommunications as infrastructure for economic and social development. It was shown that telecommunication services are used in connection with a wide range of economic production and distribution activities, delivery of social services and government administration. They also contribute to the quality of life and social, political and security objectives. Where available, telecommunications benefit a broad cross- section of the urban and rural population by income, education and occupation. These features result in high social and private returns from telecommunications investment, as well as in a considerable financial resource mobilization capacity. Information is regarded today as a fundamental factor of production, alongside capital and labor. The information economy accounted one-third to one half of gross domestic product (GDP) and of employment in Organization for Economic Cooperation and Development (OECD) countries in the 1980s and is expected to reach 60 % for the European Union (EU) in the year 2000. Information also accounts for substantial proportion of GDP in the newly industrialized economies and the modern sectors of developing countries. This increasing information intensity of economic activity, coupled with the globalization of capital flows, trade, manufacturing and other activities, resulted in strong demand for better, more varied, and less costly communication and information services. Demand growth has been challenged with rapid changes in telecommunications technology fueled by advances in microelectronics, software and optics. These changes have greatly reduced the cost of information transmission and processing. It changed the cost structures of telecommunications and many other industries, made possible new ways of meeting a wider range of communication needs at lower cost, reduced user dependence on established operating entities and increasingly integrated information and telecommunications technologies and services. Obviously these interrelated market and technological processes show no signs of decreasing or abating. In this context, telecommunications is now widely considered a strategic investment to maintain and to develop competitive advantage at all levels including national, regional and firm. Telecommunications constitute the core of, and provide the infrastructure for the information economy as a whole. Telecommunications facilitates market entry, improve customer service, and reduce costs, and increase productivity. They are an integral part of financial services, commodities markets, media, transportation, and the travel industry, and provide vital links among manufacturers, wholesalers, and retailers. Moreover, industrial and commercial competitive advantage is now not only influenced by availability of telecommunications facilities, but also by choice of network alternatives and control to reconfigure and manage networks in line with corporate objectives. Countries and firms that lack access to modern telecommunication and information systems cannot effectively participate in the global economy and politics. This applies to the least developed countries of Africa and Asia as much as to middle income countries, such as those in Latin America, East Asia, and Central and Eastern Europe that aspire to become industrial countries in the next decade. In that respect, this study is going to focus on the world's one of the most leading entity, European Union (EU)'s telecommunications status, Information Society and its vast project TEN (Trans European Networks) regarding its impacts on the interdependence between the European states in a broad sense, from politics, economics to social living. While doing it, after the introduction, the general developments of telecommunications in Europe will be mentioned by overlooking the regulatory progress in EU in part 2. With the beginning of part 3, the fundamental framework called Information Society (IS) is going to be explained by stressing on the aims and principles of this new era. However, beside its tremendous effects, living and working in IS brings up major questions. Basically, the two opposite ideas are in the minds of the people; on the one hand some says the new technologies and IS creates new fields of job and will bring profound dynamism to the every field of the life and on the other hand some says the new technologies and IS destroy more jobs than it creates, also it will create big gap between rich and poor regions, including people. However, the aim of this work is not to decide which is true or not, but to indicate two sides of the coin as clear as possible which will be done in part 4. In part 5, the way of Europe through IS will be stressed on the necessary suggestions of Commission. With the beginning of part 6 the very important IS project of EU, Trans European Networks (TENs) which is a very extended project, another words it is an advanced infrastructure which will pull Europe together to create a strong economy and better quality of life will be defined in part 6. Part 6 also highlights the main framework of TENs as TENs for Telecommunications and TEN related IS Projects of EU. After a general idea given by part 6 about TENs, part 7 will be dealt with Community Support Program for Trans European Telecommunication Networks. The idea here is to comprehend the telecommunication related services and necessary applications in order to see their effect on IS through its expansion in Europe. Even though this work does not have a comparative character, lastly, in part 8 the situation of Turkey, regarding telecommunications and IS will be described. As it is mentioned the idea here is not to compare Turkey's situation with the EU countries', but it is important to give a general opinion where Turkey is. The new era is on its way. One way or another information and telecommunication is expanding into people's life if we like it or not. So that it is substantial to understand the situation of telecommunications and the Information Society in order to see our future more clearly. From now on the economical power is not sufficient if you do not have the power of information. The countries or in other words, societies which can combine economic and information power together with highly widespread telecommunication infrastructures, will be successful in the changing world. Here in this work the ultimate aim is not to discuss the technical or judicial side of telecommunications and information society, but to emphasize the importance of this new trend for countries' future.
Keywords: İletişim (Telekomünikasyon); TELEKOMÜNİKASYON-AVRUPA TOPLULUĞU